Arcangelisia flava L. Merr. Aqueous Extract Potential as a Xanthine Oxidase Inhibitor - Fatmawati; Subandrate; Rini Yana; Maharani Puspita Sari HS; Nadia Permata Sari (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Arcangelisia flava L. Merr. contains several secondary metabolites, including berberine and palmatine, which are known to have potential as inhibitors of xanthine oxidase (XO). XO is an enzyme involved in purine metabolism, catalyzing the oxidation of hypoxanthine to xanthine and then xanthine to uric acid. The community uses the stems and leaves of A. flava to maintain health by brewing them in hot water. The potential of this plant to inhibit XO using an aqueous solvent has never been studied. This study aims to assess the xanthine oxidase inhibitory activity of water extracts derived from the stems and leaves of A. flava. The study design was an in vitro experimental study conducted in the Basic Medical Chemistry Laboratory of Universitas Sriwijaya from September to December 2023. The aqueous extract of stems and leaves from A. flava was tested using an in vitro xanthine oxidase inhibitory assay, as observed through a decrease in uric acid levels via UV absorption. The stem extract exhibited stronger XO inhibition (IC50=21.15 μg/ml, 95% CI=19.87–22.51) compared with the leaf extract (IC50=68.42 μg/ml, 95% CI=61.35–76.28). The inhibitory activity of the stem extract approached that of allopurinol (IC50=16.78 μg/ml, 95% CI=15.62–18.02). In conclusion, the aqueous stem extract of A. flava demonstrates significantly XO inhibitory activity than the aqueous leaf extract.